A Unique Case for Spinal Cord Stimulation: Successful Treatment of Small Fiber Neuropathy Pain Using Multiple Spinal Cord Stimulators. (16th July 2017) - Eckmann, Maxim; Papanastassiou, Alexander; Awad, Mark
Abstract : Spinal cord stimulators have commonly been used to treat multiple pain conditions. This case report represents a unique case of using multiple spinal cord stimulators for widespread small fiber neuropathy pain. This case report concerns patient JJ who first presented with generalized neuropathic pain. His pain was an intermittent burning, stinging quality that originally focused in both of his feet and progressed to include his legs and arms and eventually involved his entire body. The pain would last moments to hours at least daily. He reported a poor quality of life. He was diagnosed with small fiber neuropathy with anhydrosis, suggestive of idiopathic erythromelalgia. He had a spinal cord stimulator trial involving both cervical and lower thoracic percutaneous leads. After two spinal cord stimulators were implanted, the patient began to report an improvement in pain. The patient continues to report excellent pain relief. The patient uses the stimulator intermittently as needed, in an abortive fashion for pain flares. The patient is very pleased and has increased his activity. He now attends graduate school full time. This case report hopes to illustrate a unique use of multiple spinal cord stimulators in treating widespread neuropathic pain caused by small fiber neuropathy.